TEKNOLOGI PENGELOLAAN LIMBAH CAIR YANG IDEAL UNTUK PABRIK KELAPA SAWIT - Rahardjo, Petrus Nugro (Jurnal Air Indonesia, 2006)
The number of crude palm oil factory (CPOF) in Indonesia has already increased rapidly in the last fifteen years. In the same period, expansion of the palm plantation has also been continuing and growing, but unfortunately the accelerated growth is not same as the development of the wastewater treatment technology and its proper applications. Many CPOF in Indonesia have not a good wastewater treatment plant (WWTP). In fact they cause terribly environmental problems, especially related to surface water pollution. BOD content in the effluent of most CPOF is between 35,000 to 46,000 ppm and in the effluent of their WWTP it is much more than 100 ppm. Therefore it needs to propose a treatment system which can guarantee to reduce all pollutants till a value matching with the environmental quality standard. Based on the research result assessed by BPPT, an ideal WWTP suitable for CPOF is promoted to be considered as one very good alternative which is better applied for all CPOF in Indonesia. The stages and processes are showed in the second figure. Key words : Ideal treatment, CPOF wastewater